KURIKULUM PENDIDIKAN TINGGI KEAGAMAAN ISLAM: MUTU DAN RELEVANSI - Alhamuddin Alhamuddin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstract: World Bank Report (2013) mentioned that the higher education system is currently lacking to respond to the dynamics of the job market thus causing a mismatch of skills are n eeds to be improved. Based on these results, universities need to increase understanding about the curriculum and parse the skills mismatch. Specifically, the comprehensive conduct the mapping related to demand and supply of skills in different sectors and the needs of society. Such mapping exercises will only be useful if the pattern of gathering information on the need for improved and involve all stakeholders who have a requirement to graduate of higher education itself.Keywords; Higher Education, Curriculum, Relevant, Quality